Respostas
respondido por:
1
2x-5x = -1-5
3x = -6
x = 3 : -6
x = -2
3x = -6
x = 3 : -6
x = -2
respondido por:
1
A)
2x+5-5x=-1
2x-5x=-1-5
-3x=-6 (-1)
3x=6
x=6/3
x=2
Resposta: 2
B)
5+6x=5x+2
6x-5x=2-5
x=-3
Resposta: -3
C)
x+2x-1-3=x
x+2x-x=1+3
2x=4
x=4/2
x=2
Resposta: 2
2x+5-5x=-1
2x-5x=-1-5
-3x=-6 (-1)
3x=6
x=6/3
x=2
Resposta: 2
B)
5+6x=5x+2
6x-5x=2-5
x=-3
Resposta: -3
C)
x+2x-1-3=x
x+2x-x=1+3
2x=4
x=4/2
x=2
Resposta: 2
NathyOliveiraaa:
Muito obrigado
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás